Inflence of Electric Field on the Melting Characteristics Burning Wax - Orlovska, S.G. (Physics and Chemistry of Solid State, 2015)
A study of influence of homogeneous electric-field is undertaken on the processes of melting and burning of particles to the octadecane in mid air. It is shown that in the electric field on the initial stage diminishes speed of melting that results in the increase of time of melting. It is set that under act of electric-field there is an increase of speed of burning of drops to the octadecane and displacement of flame in direction of electric-field.